2009
DOI: 10.1007/s10654-009-9335-x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of coronary heart diseases and heart failure based on hospital discharge and mortality data in the Netherlands using the cardiovascular registry Maastricht cohort study

Abstract: Incidence rates of cardiovascular diseases are often estimated by linkage to hospital discharge and mortality registries. The validity depends on the quality of the registries and the linkage. Therefore, we validated incidence rates of coronary heart disease (CHD), acute myocardial infarction, unstable angina pectoris, and heart failure, estimated by this method, against the disease registry of the cardiovascular registry Maastricht cohort study. The cohort consists of 21,148 persons, born between 1927 and 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 26 publications
3
116
0
Order By: Relevance
“…In a subsample of the cohort, cases of coronary heart disease (CHD; defined as International Classification of Diseases, Ninth Revision [ICD‐9] codes 410–414) obtained from hospital discharge diagnoses were verified against medical records. This showed that 85% of CHD events and 97% of acute myocardial infarctions could be confirmed 15. Follow‐up was complete until January 1, 2008.…”
Section: Methodsmentioning
confidence: 91%
“…In a subsample of the cohort, cases of coronary heart disease (CHD; defined as International Classification of Diseases, Ninth Revision [ICD‐9] codes 410–414) obtained from hospital discharge diagnoses were verified against medical records. This showed that 85% of CHD events and 97% of acute myocardial infarctions could be confirmed 15. Follow‐up was complete until January 1, 2008.…”
Section: Methodsmentioning
confidence: 91%
“…Another strength of our study is the use of reliable and validated registries such as the NIVEL influenza-like illness registry, the Dutch HDR and CDR, and the ECA data set of daily temperature values. 12,28,33,34,38,45,56 Another strength of our study is the analysis, in which we used 1) population-based SAH incidence data from 12 European countries and 2) data on mean daily temperature from the ECA data set, to confirm the association between cold temperature and SAH found in our nationwide analyses. A limitation of the present study may be that we only used daily temperature data from European countries, which might affect the generalizability of our findings to non-European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for outcomes with many minor events, we may underestimate the associations, as misclassification is more likely than for outcomes with more severe events. This may have resulted in weaker associations (39), which may not necessarily reflect a weaker biological association.…”
Section: Discussionmentioning
confidence: 99%